A study of impact of body mass index (BMI) toward fitness among firefighters in Kuantan - Nur Aisyah, Rozak (2018)
This study is about the impact of Body Mass Index (BMI) toward fitness among firefighters in Kuantan. The main objective of this study was to determine association between BMI and fitness of firefighters in Kuantan. BMI can be categorized as underweight, healthy range, overweight and obese. The component of fitness such as flexibility, muscular power and muscular endurance. Male firefighters (n=60) were selected randomly from three fire station in Kuantan. The fitness can be measure by series of test like sit and reach test, push-up test, sit up test and standing broad jump test. Correlation method are used for relate the BMI and fitness among firefighters. Mean (SD) for each variable which is BMI 26.32(3.93), sit and reach 26.96(11.82), push-up 28.58 (15.44), sit-up 19.97 (9.14), standing broad jump 131.28 (101.28), age 37.95(6.38), smoking status 2.38 (1.27), working experience 3.22 (1.44) and often workout 2.50 (0.89). The result show BMI and fitness have relationship to each other. Age give effects on fitness level of firefighters. In a conclusion, body mass index in a healthy range can improve the firefighter's performance because BMI influence the fitness.